Education of Today Is the Security of Tomorrow!: Strengthening the Capacities to Create Secure Environments with Cultural Education - Vergin, Raphael (Archīum Ateneo, 2024)
Human security as a people’s perspective on security with a focus on human well-being and relationship-building offers promising alternative concepts to state-centered and structure- focused security strategies. Security is more than increasing weapons, fences and survey cameras. To our understanding, it is something else and involves entirely different mindsets. It demands a people’s perspective on security in which citizenship includes the capacity to create secure surroundings. People can be supported to “learn” security and to focus on their capacities. The subjective dimensions of security, including a person’s emotional management, can be trained. This is why we argue that three dimensions of training have to be integrated into educational approaches. First among these dimensions is tackling cultural violence through working on stereotypes and prejudices by delivering knowledge and information. Second is fostering knowledge about relationship-building and building relationships across the social divide. And third is strengthening the self-esteem of the citizens and focusing on their personal development and well-being. Hence, new approaches of experience-based learning and group work have to be integrated into the formal and informal curricula. Thus, we advocate for enriching formal and informal education with training modules in “peace and security”—training for everybody, so that our education of today makes us ready for the threats of tomorrow. We argue further that this can only be accomplished if experience-based methodological tools, such as interactive theater, are included in these trainings.